Peran Mata Kuliah Bahasa Indonesia Dalam Membentuk Kemampuan Komunikasi Matematis Pada Mahasiswa Pendidikan Matematika Angkatan 2025 Universitas Negeri Gorontalo - Alya A.M Aritan; Rahmatika Mosi; Mirna Hanapi; Moh. Awaludin Lamuhu; Niar Hidaya S Yamaa; Tris Mooduto; Sariva Lamadaju; Frisya Kuyo; Aidhil Akbar; Nur Fadilah Polihito; Meilina Widya Dali (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2026)
Mathematical communication is an essential competence for prospective mathematics teachers because mathematical ideas must be expressed through clear, logical, and coherent language. This study describes students' perceptions of the contribution of the Indonesian Language course to written and oral mathematical communication. Using a descriptive qualitative approach, data were collected from active Mathematics Education students, Class of 2025, at Universitas Negeri Gorontalo through a hybrid questionnaire via Google Forms. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings show that effective sentences, paragraph organization, academic diction, and logical reasoning help students write problem-solving reports, construct mathematical arguments, and present mathematical ideas more coherently. The course therefore has a strategic role as a foundation for academic communication, although its materials need to be contextualized through mathematics-based scientific writing, presentation, and rhetorical practice.